Plan de negocios para la creación de una empresa dedicada a la elaboración y exportación de barras energéticas a base de granola y jalea de guayusa a Singapur - Loza Mendoza, Juan Carlos (2014)
The purpose of this business plan is to determine the viability of developing and exporting energy bars made with granola and guayusa jelly to the Republic of Singapore. The business of energy bars is in the industry of Bakery Manufacture, This HS code is not exported from Ecuador to Singapore yet, but it has a exportable potential of USD 12.776.000,00. The Market Intelligence was made on 3 countries: South Korea, Singapore and the UK, it was determined that the Republic of Singapore is a promising market due their westernized culturally, zero total agricultural production and trade openness. The bars will be named NATIVE, they will be entering the Singapore market through a differentiation strategy due to the product is natural, it has all the Certifications that the Singapore government requires in order to entry food to the country and it has the entering the Singapore market through differentiation strategy as the product is natural, is certified that the Singapore government requires for entry food and also it has the guayusa ingredient that no other bar in Singapore has. The moment the brand is positioned in the trade, the market penetration strategy will be used, whereby it is intended that existing customers to buy more product. The company will have people committed to the institutional values of the organization, and accounting and legal advice will be subcontracted. The initial investment is USD 123.236,00 this investment includes the amounts of fixed assets, intangible assets and working capital. The capital structure is formed by a gearing of 40% and 60% equity. Financially this business plan is viable and due to all three scenarios yields a positive NPV and the internal rate of return of the plan is greater than the opportunity cost. The development of this plan with the expected scenario will get a NPV of USD 140,391.00 and an IRR of 28.91%. The return of the investor will be four years with a profit of a 28.58% concluding the feasibility of implementation, taking into account the research carried out, so the implementation of the business plan is recommended.